The Collaborative Assessment and Management of Suicidality compared to enhanced treatment as usual for inpatients who are suicidal: A randomized controlled trial - Santel, Miriam; Neuner, Frank; Berg, Michaela; Steuwe, Carolin; Jobes, David A.; Driessen, Martin; Beblo, Thomas (Frontiers in Psychiatry, 2023)
Background Although use of inpatient crisis hospital intervention for suicide risk is common, the evidence for inpatient treatments that reduce suicidal thoughts and behaviors is remarkably limited. To address this need, this novel feasibility pilot randomized controlled trial compared the use of the Collaborative Assessment and Management of Suicidality (CAMS) to enhanced treatment as usual (E-TAU) within a standard acute inpatient mental health care setting. Objectives We hypothesized that CAMS would be more effective than E-TAU in reducing suicidal thoughts and behaviors. As secondary outcomes we also investigated depressive symptoms, general symptom burden, reasons for living, and quality of the therapeutic relationship. Methods All patients were admitted due to acute suicidal thoughts or behaviors. They were randomly assigned to CAMS (n = 43) or E-TAU (n = 45) and assessed at four time points (admission, discharge, 1 month and 5 months after discharge). We used mixed-effects models, effect sizes, and reliable change analyses to compare improvements across and between treatment groups over time. Results Intent-to-treat analyses of 88 participants [mean age 32.1, SD = 13.5; n = 47 (53%) females] showed that both groups improved over time across all outcome measures with no significant between-group differences in terms of change in suicidal ideation, depression, reasons for living, and distress. However, CAMS showed larger effect sizes across all measures; for treatment completers CAMS patients showed significant improvement in suicidal ideation (p = 0.01) in comparison to control patients. CAMS patients rated the therapeutic relationship significantly better (p = 0.02) than E-TAU patients and were less likely to attempt suicide within 4 weeks after discharge (p = 0.05). Conclusions CAMS and E-TAU were both effective in reducing suicidal thoughts and symptom distress. Within this feasibility RCT the pattern of results was generally supportive of CAMS suggesting that inpatient use of CAMS is both feasible and promising. However, our preliminary results need further replication within well-powered multi-site randomized controlled trials. Trial registration DRKS-ID/ICTRP-ID: DRKS00013727. The trial was retrospectively registered in the German Clinical Trials Register, registration code/ DRKS-ID: DRKS00013727 on 12.01.2018 and also in the International Clinical Trials Registry Platform of the World Health Organization (identical registration code).